2014
DOI: 10.1002/bjs.9663
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of ultrasound-guided biopsy of suspicious axillary lymph nodes in the selection of patients with extensive axillary tumour burden in breast cancer

Abstract: Patients with breast cancer in whom axillary metastases are detected by ultrasound-guided biopsy have significantly more involved nodes than SLNB-positive patients. This finding enables further preoperative tailoring of axillary treatment in breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
40
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 42 publications
7
40
0
Order By: Relevance
“…Furthermore, while survival was expectedly worse in the needle biopsy cohort reported by Verheuvel el al that presented with more advanced-stage disease, there was no difference in regional recurrence, with only one isolated regional relapse in each group.. A meta-analysis including 6 additional studies also reported a higher percentage of pN2 disease in women with a positive needle biopsy compared to those with negative axillary imaging with a positive sentinel lymph node (46% versus 30%). 16 These studies concluded that SLNB may not be appropriate for women diagnosed with nodal disease by US and needle biopsy because this represents a higher-risk population; however, these studies do not represent women meeting Z0011 criteria, and yet 30%–52% of patients had low volume nodal disease and, in the appropriate context, could be spared ALND.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, while survival was expectedly worse in the needle biopsy cohort reported by Verheuvel el al that presented with more advanced-stage disease, there was no difference in regional recurrence, with only one isolated regional relapse in each group.. A meta-analysis including 6 additional studies also reported a higher percentage of pN2 disease in women with a positive needle biopsy compared to those with negative axillary imaging with a positive sentinel lymph node (46% versus 30%). 16 These studies concluded that SLNB may not be appropriate for women diagnosed with nodal disease by US and needle biopsy because this represents a higher-risk population; however, these studies do not represent women meeting Z0011 criteria, and yet 30%–52% of patients had low volume nodal disease and, in the appropriate context, could be spared ALND.…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity of axillary ultrasound (in combination with tissue sampling where deemed necessary) is approximately 80% [15]. Furthermore, a negative axillary ultrasound excludes the presence of four or more lymph node metastases, with a negative predictive value of 93–96% in the general breast cancer population [1618]. Therefore, axillary ultrasound improves preoperative selection of node negative patients, as it selects patients with a more favourable tumour load and confidently excludes advanced nodal disease.…”
Section: Introductionmentioning
confidence: 99%
“…While the ACOSOG Z0011 trial identified clinically node-negative patients by physical exam alone, some have suggested that axillary imaging with or without needle biopsy may be beneficial to allocate high-risk node-positive patients directly to ALND 9-13 , omitting SLNB and the possible need for two-step axillary surgery. However, when managing patients according to ACOSOG Z0011, preoperative axillary imaging is only beneficial if it accurately discriminates between patients with metastases in 1 or 2 axillary nodes and those with involvement of 3 or more nodes or gross extracapsular extension (matted nodes) who require ALND.…”
Section: Introductionmentioning
confidence: 99%